Correlation between the non-use of cooking oil fume extractors and bone mineral density in population aged 45 years and older in China: a cross-sectional study - Zhang, Haitao; Shi, Binhao; Yuan, Chunchun; Huang, Chen; Huang, Tingrui; Liao, Zhangyu; Zhu, Wenhao; Zhong, Wei; Xu, Hongbin; Ji, Jiangxun; Cai, Feihong; Chen, Yue; et al. (Frontiers in Endocrinology, 2024)
Introduction: The correlation between the non-use of cooking oil fumes (COFs) extractors and bone mineral density (BMD) have not been clarified. Consequently, this study attempted to explore the impact of non-use COFs extractors on BMD in population aged 45 years and older based on a cross-sectional study. Methods: This study was a cross-sectional study within the framework of an ongoing prospective population-based cohort study in China. The multiple logistic regression model was used to evaluate the correlation between the use of fume extractors in family cooking and total lumbar spine (LS), femoral neck (FN), total hip BMD and levels of bone metabolism markers. Results: A total of 3433 participants were included in the final analyses, of which 2607 (75.93%) participants used fume extractors. The results of models indicated that there were significant correlations of the non-use of fume extractors on total LS BMD (β = -0.024, 95% CI, -0.036, -0.012, p < 0.001), PINP (β = 4.363, 95% CI, 2.371, 6.356, p < 0.001) and ALP (β = 4.555, 95% CI, 2.593, 6.517, p < 0.001) levels. Conclusions: This study verified that the use of fume extractors is an efficacious measure to prevent LS bone loss. For the sake of public bone health, people should install a fume extractor in the kitchen and use it routinely when cooking.